Antifouling agent, micro-nano mesoporous material and marine antifouling composition

By covalently linking DCOIT-like derivatives with activated silicon hydroxyl groups, the antifoulant molecules are locked in modified sepiolite fibers, the problems of long-term antifoulant and insufficient drug loading in the prior art are solved, and efficient and long-term marine antifoulant performance are achieved.

CN119591557AActive Publication Date: 2025-03-11POWERCHINA ZHONGNAN ENG

Patent Information

Application Number
CN202510138841.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-11
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The prior art has shortcomings in effectively preventing sea organisms from adhesion and reproduction, especially in terms of long-activity and drug loading, and antifoulants are easily dissolved by solvents or seawater, resulting in excessive release.

Method used

By covalently linking DCOIT-like derivatives with activated silicon hydroxyl groups, strengthening bonds are formed, and antifouling agent molecules are locked in modified sepiolite fibers to form organic-inorganic hybrid materials, achieving high-throughput loading and sustained release.

Benefits of technology

It achieves efficient and long-term marine anti-fouling performance, with a drug load of 60.6%, and through the encapsulation of strengthened bonds, the excessive release and dissolution of antifouling agents are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591557A_ABST
    Figure CN119591557A_ABST
Patent Text Reader

Abstract

The invention discloses an antifouling agent, a micro-nano mesoporous material and a marine antifouling composition. A preparation method of the micro-nano mesoporous material comprises the following steps: S1, sequentially carrying out hydrothermal acid etching, cleaning, roasting and cooling on a micro-nano mesoporous material matrix for later use; s2, dissolving a DCOIT-like derivative and halogenated fatty alcohol in a solvent, heating and refluxing, dropwise adding a mixed solution of diisocyanate and a catalyst, and continuously carrying out heat preservation reaction; and S3, grinding and bulking the micro-nano mesoporous material modified matrix prepared in the step S1 to fully release agglomerated fiber bundles, ultrasonically dispersing the fiber bundles in a solvent, adding the dispersed fiber bundles into a system in the step S2, carrying out a heating reaction, purifying, drying, grinding, and storing. Activated silicon hydroxyl enriched in a micro-nano mesoporous material modified matrix is covalently linked with degradable terminal isocyanate (R-NCO) in quaternized DCOIT derivatives, and the method has the properties of high efficiency, broad spectrum, low toxicity and long-acting effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic-inorganic hybrid functional materials, and specifically relates to an antifouling agent, a micro-nano mesoporous material and a marine antifouling composition. Background Art

[0002] The attachment and reproduction of marine organisms have a serious negative impact on marine engineering and national defense construction. It not only reduces the speed of ships and significantly increases fuel consumption, but may also cause instability of facilities / platforms. Their acidic secretions will also aggravate metal corrosion. How to effectively deal with marine biofouling has always been a global and century-old problem. Among the many protective measures, the application of antifouling coatings is undoubtedly one of the most economical, simple and ideal means.

[0003] The key component of antifouling coatings is the antifouling agent system, which should have the characteristics of low toxicity, high efficiency, broad spectrum, and long-term effect, so as to efficiently kill as many adhering biological populations as possible without destroying the marine ecology, and at the same time be able to maintain a long-term and continuous effect.

[0004] Tributyltin (TBT) was once widely used worldwide due to its excellent anti-fouling ability, but it was later discovered that tin can disrupt the endocrine system of organisms and its metabolite toxicity is as high as 100-400µg / L. It has been completely banned by the International Maritime Organization since 2008. 4,5-Dichloro-2-octyl-4-isothiazoline-3-one (DCOIT) is the first green antifouling agent with minimal bioaccumulation (half-life ≤ 1h) registered by the EU BPD (metabolite toxicity > 125mg / L, acute oral L in rats) D 50 >2800mg / kg, rabbit acute percutaneous L D 50 >5000mg / kg), with incomparable environmental protection and universality of TBT, it can effectively inhibit and kill the clinging growth of fungi (such as molds, yeasts), bacteria, algae, mucus, seaweed, anemones, tunicates, sponges (the so-called "soft fouling organisms"), and hard-shelled invertebrates such as barnacles and tubeworms ("hard fouling organisms"). DCOIT and its derivatives are regarded by the industry as the only choice for current general marine antifouling agents. In order to obtain long-term antifouling performance, researchers have spared no effort to transform it into a slow-release system in multiple ways.

[0005] The following patents with publication numbers CN102293198B, CN101137288B, KR101253065B1, JP2008513475A, and WO2006032019A1 use DCOIT as the core material and develop water-in-oil core-shell structure microcapsules through multiple processes. The microcapsules have good sustained release properties, and the release amount is less than 10% after immersion in xylene for 90 days. Zhou Yaoru (Fine and Specialty Chemicals, 2024, 32(2):39-44) also synthesized DCOIT@HACC-SA (quaternary ammonium salt chitosan-sodium alginate) microcapsules, but the initial exudation is too fast (75.4% burst release within 12 days), which is difficult to meet the long-term antifouling needs of the ocean.

[0006] In addition to microencapsulation, it is also a common practice to physically adsorb DCOIT on the surface of micro-nano particles with high specific surface area or / and in the internal pores by using intermolecular hydrogen bonds, van der Waals forces, electrostatic coupling, etc. Wang Xiaowei (Fine Chemicals, 2007, 24(10):944-947; 2007, 24(3):213-220) encapsulated DCOIT with copper microspheres and nano-titanate tubes, respectively, but the drug loading was low, with the maximum being only 15.2% and 12%. The following patents with publication numbers US6676954B2 and CN1229022C disclose a controlled release composition, in which the DCOIT antifouling coating adsorbed with different activated carbons releases 53% (C-1 carbon type) in 21 days in artificial seawater or releases 50% in only 30 days (C-2 carbon type), which is also only suitable for short-term antifouling.

[0007] The patent with publication number CN115141508B provides a long-lasting metal organic framework-supported antifouling agent and its preparation method, which relies on BIT-NH 2 The interaction between quaternary ammonium salt and UiO-66-COOH framework resulted in a significant sustained release of BIT in artificial seawater. It took 45 days and 47 days for 50% release at 39.75% and 40.51% loading, respectively. Similarly, Zhang Xin (Surface Technology, 2024, 53(8):107-118) successfully encapsulated carboxylated 1,2-benzisothiazolin-3-one (BIT-COOH) in amino ZIF-7 (NH 2 -ZIF-7) nanocages, with stable sustained release and excellent antibacterial / algae properties.

[0008] The patent with publication number CN110835495B provides a moisture-curing polyurethane antifouling coating for fishing nets and a preparation method thereof. The linear hydroxyl-terminated polycaprolactone resin is aminated with diisocyanate and cross-linked with the help of water vapor. The paint film can meet the flexibility requirements of the fishing net, but the selected diatomaceous earth, sepiolite, and calcined kaolin porous fillers have not been modified by expansion or other modification treatments, and the brominated pyrrole nitrile and DCOIT biocide are only simply adsorbed, and the drug loading is unknown.

[0009] In general, microencapsulation or physical adsorption has its own advantages in controlled release. The drug loading of microcapsules can be adjusted by the size of the capsule, but the preparation process is relatively complicated; in addition, the simple oil-in-water or water-in-oil configuration may also be swollen by the organic solvent or seawater in the antifouling coating, causing the capsule to stick and the capsule wall to rupture, resulting in excessive and rapid dissolution of the antifouling agent core. The intermolecular force of physical adsorption is weak, and the antifouling agent is easy to desorb (fall off from the carrier). In addition, the pores of natural porous materials (such as carbon nanotubes, halloysite, montmorillonite, zeolite, etc.) are narrow, mostly mesoporous (2-50nm), and the volume is limited. The difference in compatibility between inorganic powders and organic film-forming resins in antifouling coatings also makes the antifouling agent embedding system easy to settle and separate. Summary of the invention

[0010] Based on the above defects, the purpose of the present invention is to disclose an antifouling agent, a micro-nano mesoporous material and a marine antifouling composition. The micro-nano mesoporous material matrix is ​​expanded by hydrothermal acid etching, and the enriched activated silanol group is covalently linked with the degradable terminal isocyanate (R-NCO) in the quaternized DCOIT derivative, and the organic antifouling agent guest molecule is firmly locked in the micro-nano mesoporous material modified matrix through strong chemical bonds with high throughput, which is green and environmentally friendly and has long-lasting and slow-release antifouling performance.

[0011] To achieve the above purpose, the technical solution of the present invention is as follows: An antifouling agent, the structure of which is as shown in general formula I: ; In formula I, m and n are respectively non-zero natural numbers, and X is a halogen.

[0012] The invention also discloses a micro-nano mesoporous material, comprising a micro-nano mesoporous material matrix and the antifouling agent, wherein the activated silanol groups in the micro-nano mesoporous material matrix are covalently connected with -NCO units in the antifouling agent.

[0013] The micro-nano mesoporous material refers to a material with a pore size between 2 and 50 nm and a high specific surface area (BET ≥ 150m 2 / g), inorganic, organic or organic-inorganic hybrid materials with good adsorption / catalytic activity and complex pore structure.

[0014] The antifouling agent is prepared by reacting a DCOIT-like derivative, a halogenated fatty alcohol and a diisocyanate.

[0015] In a preferred embodiment of the present invention, the micro-nano mesoporous material matrix includes one or more of sepiolite, halloysite, montmorillonite, zeolite, gas silica and organic metal framework.

[0016] In a preferred embodiment of the present invention, the micro-nano mesoporous material matrix is ​​sepiolite, and the micro-nano mesoporous material structure is as follows:Figure 1 shown.

[0017] Figure 1 In the figure, the hollow tubes represent the porous fibers of sepiolite 1, and the black curves represent the long chains of antifouling agents 2 chemically loaded with active silanol groups on the surface and inside of sepiolite.

[0018] In a preferred embodiment of the present invention, when the micro-nano mesoporous material matrix is ​​sepiolite, the particle size of the micro-nano mesoporous material matrix is ​​200-3000 mesh. The particle size of the micro-nano mesoporous material matrix is ​​preferably 800-2000 mesh. Within this particle size range, the sepiolite fiber has a regular morphology, good adjustability of drug loading, and a high degree of matching with the antifouling composition.

[0019] In a preferred embodiment of the present invention, the preparation method of the micro-nano mesoporous material comprises the following steps: S1, subjecting the micro-nano mesoporous material matrix to hydrothermal acid etching, washing, roasting, and cooling for standby use; S2, dissolving the DCOIT-like derivative and the halogenated fatty alcohol in a solvent, heating to reflux, and then dropping a mixture of diisocyanate and a catalyst to continue the reaction at a constant temperature; S3, grinding and dispersing the modified matrix of the micro-nano mesoporous material obtained in S1 in a solvent, adding it to the S2 system for a temperature reaction, and then purifying, drying, grinding, and storing it.

[0020] In a preferred embodiment of the present invention, the acid etching in step S1 is carried out using 8-10 wt% dilute hydrochloric acid. Preferably, the micro-nano mesoporous material matrix is ​​dispersed in dilute hydrochloric acid to form a suspension containing 3-5 wt% solids, and magnetic stirring is performed at 50-60° C. for 10-12 h; the calcination temperature is 200-300° C., and the calcination time is 1-2 h; the washing step is carried out using saturated NaHCO 3 Wash until the solution is neutral.

[0021] The molar ratio of the DCOIT-like derivative, the halogenated fatty alcohol, and the diisocyanate in S2 is 1:(1-1.1):(1.1-1.15). Preferably, the DCOIT-like derivative, the halogenated fatty alcohol, the diisocyanate, and the solvent are all dried to remove water in advance, and the reaction is carried out in the whole process. 2 Atmosphere protection and continuous stirring; further preferably, a quaternary ammonium catalyst is also added to S2, including one or a combination of NaI and KI, and the molar mass ratio of the DCOIT-like derivative to the quaternary ammonium catalyst is 40-60 mmol: (40-60) mg.

[0022] Preferably, in S2, the reflux temperature is 40-50°C, the reflux time is 10-12 hours, and the subsequent insulation time is 6-8 hours.

[0023] Preferably, the heating temperature in S3 is 60-70° C., and the reaction time is 5-6 h.

[0024] In a preferred embodiment of the present invention, the structure of the DCOIT-like derivative is as shown in the general formula II: ; In Formula II, R 1 , R 2 are independently selected from -H, -Cl, -Br, -I; R 3 is any one of -H, aliphatic alkyl, aralkyl, alkoxy, alkenyl, and alkynyl. 1 , R 2 All are -Cl, R 3 For -C 8 H 17 .

[0025] DCOIT-like derivatives include DCOIT and its derivatives.

[0026] DCOIT and its derivatives have strong penetration into biological cell membranes and cell walls, and can interact with sulfur-containing proteins, enzymes or active small molecules in cells (breaking SN bonds and forming SS bonds), thereby destroying the ability of cells to divide and proliferate. By comparison, it was found that when there are large-volume substituents (such as benzene rings, long-chain aliphatic alkanes) or electron-withdrawing groups (ether bonds, carbonyl groups) on the N atom or more halogen atoms on the isothiazolinone ring, its biological activity is relatively strong. Based on this and combined with comprehensive considerations such as market scale and price, R 1 , R 2 All are -Cl, R 3 For -C 8 H 17 .

[0027] In a preferred embodiment of the present invention, the halogenated fatty alcohol includes one or more of chlorinated, brominated, iodinated, and fatty alcohols containing 1 to 8 carbon atoms; The diisocyanate is an α, ω-terminated diisocyanate fatty acid ester and its derivatives, including one or more of 2,3-diisocyanatopropionate, 2,4-diisocyanatobutyrate, 2,5-diisocyanatovalerate, 2,6-diisocyanatohexanoate, 2,7-diisocyanatoheptanoate, 2,8-diisocyanatooctanoate, 2,9-diisocyanatononanoate, 2,10-diisocyanatodecanoate and their derivatives.

[0028] In view of factors such as the reactivity of the halogenated compound, the selling price, and the ease of degradation, the halogenated fatty alcohol is preferably 6-bromo-1-hexanol; the diisocyanate is preferably one or a combination of 2,5-diisocyanatoethyl valerate and 2,6-diisocyanatoethyl hexanoate.

[0029] 2,5-Diisocyanatoethyl valerate and 2,6-Diisocyanatoethyl hexanoate are modified products of ornithine and lysine respectively. Both are green and renewable, can be purchased on the market, have a moderate molecular chain length and can be completely degraded. Other non-natural diisocyanates, such as toluene diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate units selected in the patent with publication number CN110835495B, are non-degradable and can only disintegrate into "microplastics" (the degradation described in the patent essentially only occurs in the polycaprolactone segment), and their environmental protection needs to be improved.

[0030] The solvent used in S2 and S3 is one or more of ethyl acetate, xylene, methanol, chloroform, acetonitrile, and butyl acetate.

[0031] The catalyst in S2 is one or both of diisobutyltin dilaurate and stannous isooctanoate.

[0032] In S3, the modified matrix of the micro-nano mesoporous material obtained in S1 is ground and fluffed to fully loosen the agglomerated fiber bundles, and then ultrasonically dispersed in the solvent to facilitate the deep penetration of the solvent and the reaction molecules into the interior.

[0033] The present invention also discloses a marine antifouling composition, which comprises, by weight, 10 to 30 parts of the micro-nano mesoporous material, 25 to 45 parts of cuprous oxide, 5 to 10 parts of zinc pyrithione, 30 to 40 parts of hyperbranched zinc resin, 3 to 5 parts of modified rosin, 1 to 3 parts of polyethylene wax, 0 to 3 parts of chlorinated paraffin, 0 to 10 parts of filler, 0 to 3 parts of red iron oxide, and 10 to 20 parts of an organic solvent.

[0034] Preferably, in the marine antifouling composition, the filler is selected from one or more of talc, titanium dioxide, silica powder, and calcium carbonate powder; and the organic solvent is a mixture of xylene and n-butanol in a mass ratio of (1-3):1.

[0035] Compared with the patent with publication number CN110835495B, the biocide in this scheme relies on weak interactions such as hydrogen bonds to be physically adsorbed in the porous filler, and the terminal isocyanate polyester resin is cured into a film with moisture. The formed paint film can be slowly hydrolyzed, and the antifouling agent in the coating is released at the same time. The present invention forms a covalent link between the micro-nano mesoporous material modified matrix and the DCOIT-like derivative through a carbamate reaction. The DCOIT-like derivative is a quaternized DCOIT-like derivative, so that the organic antifouling agent guest molecule is firmly encapsulated in the micro-nano mesoporous material modified matrix through a strong chemical bond. The bonding principle is very different from the patent with publication number CN110835495B. In addition, the filler involved in the patent with publication number CN110835495B has not been expanded, and there is no chemical bonding between the biocide molecules, so its drug loading, actual drug release stability, and long-term effect (after 6 months) are unknown.

[0036] The preparation mechanism of micro-nano mesoporous materials is further explained as follows: The micro-nano mesoporous material matrix represented by sepiolite has a large specific surface area and complex pores, and is highly dispersible in most solvents. It is a rare natural load-bearing container, but unfortunately the pore size is generally small and the pore volume is limited. Step S1 hydrothermal acid etching treatment can further penetrate and expand the original cavity structure of sepiolite horizontally and vertically to increase the load capacity, while also removing impurities such as calcite and quartz, effectively reducing the density of magnesium-rich silicate crystals, transforming the fiber from a bundled state to a divergent state, and obtaining more and more activated silanol groups (such as Mg in the "-Si-O-Mg-O-Si-" skeleton). 2+ H + Replacement, generating Si-OH bonds). High temperature calcination (<300℃) is not only conducive to removing water molecules in various forms in the sepiolite lattice (such as adsorbed free water), avoiding the potential possibility of the latter causing the termination of the -NCO chain reaction, but also can increase the fiber specific surface area and pore size. However, it should be noted that excessive hydrochloric acid concentration (>15wt%) is prone to cause serious fiber breakage; calcination >300℃ may cause the pores to collapse, hydroxyl water to be lost (meaning no longer graftable), and even the crystal form to change completely.

[0037] Studies have confirmed that a large number of silanol groups on the surface and inside of sepiolite have a strong affinity for organic matter (especially after acid etching activation), and can be polyurethane-formed with -NCO functional groups; and the N atom on the tertiary amine of DCOIT-like derivatives contains a lone electron pair, which can be nucleophilically replaced by halogens with strong electronegativity. Based on this, DCOIT-like derivatives are quaternized into halogenated fatty alcohol salts and connected to specific diisocyanates, which gives them active sites that can covalently bond with modified sepiolite, so that the two eventually form a chemical loading method that is significantly different from physical coupling that relies on intermolecular hydrogen bonds, electrostatic forces, etc.; subsequently, the antifouling agent is slowly released through the dual degradation of amino acid esters and fatty alcohol units in the polyurethane chain segments, thereby exerting its efficacy.

[0038] Compared with the prior art, the present invention has the following beneficial effects: First, by covalently linking the activated silanol groups in large quantities in modified sepiolite fibers with the terminal -NCO in the quaternary ammonium salt of DCOIT derivatives, the guest molecules of the antifouling agent are locked in the receptor container with strong chemical bonds, which provides a feasible reference for the high added value utilization of inorganic powders and the high flux loading of marine antifouling agents; at the same time, the compatibility between inorganic powders and film-forming resins is improved after organic hybridization, and it is not easy to degrade in the composition. Subsequent micro-nano mesoporous material matrices rich in active hydroxyl groups, amine groups and other graftable groups such as halloysite, montmorillonite, zeolite, gas silica, and organic metal frameworks can all be modified by following similar processes. The obtained organic-inorganic hybrid system is much stronger than the weak interactions that rely on intermolecular hydrogen bonds, van der Waals forces, electrostatic coupling, etc., making it difficult for guest molecules to accidentally fall off (desorb) due to external stimuli such as temperature, concentration, and pressure changes. The specially selected "bridging" unit (i.e., the connecting segment between the DCOIT-like derivative and the sepiolite fiber) has a high degree of freedom of molecular rotation (good flexibility) and has dual degradation characteristics (diisocyanates and fatty alcohols can be completely degraded). After it gradually disintegrates in the natural environment, the antifouling agent is "unlocked" and can be slowly and continuously released. It is worth mentioning that the "comb"-like configuration of the organic-inorganic hybrid (sepiolite fiber is the "comb handle" and the long chain of the antifouling agent is the "comb teeth") can easily achieve more "comb teeth" by adjusting the size of the "comb handle" (selecting fibers with a large aspect ratio) (indicating a larger drug load).

[0039] Second, the preparation process of micro-nano-mesoporous materials is simple (significantly better than microencapsulation), the reaction conditions are mild, and they can be obtained by a "one-pot method". The hyperbranched zinc resin in the composition can be self-polished, and as it falls off due to water erosion, it can also play a secondary role in regulating the slow release of the antifouling agent. The combination of cuprous oxide and zinc pyrithione further strengthens and expands the broad-spectrum biocidal activity of DCOIT-like derivatives.

[0040] Based on this, the antifouling agent, micro-nano mesoporous material and the marine antifouling composition prepared therefrom firmly encapsulate the organic antifouling agent guest molecules in the micro-nano mesoporous material modified matrix through strong chemical bonds at high throughput, and have the properties of high efficiency, universality, low toxicity and long-lasting effect, and are suitable for the antifouling needs of multiple scenarios such as sports ships, offshore ranches and static platforms. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of the structure of the micro-nano mesoporous material prepared in Example 1 or 2, wherein 1 is a porous fiber of sepiolite, and 2 is a long chain of antifouling agent chemically loaded with active silanol groups on the surface and inside of the sepiolite.

[0042] Figure 2 The micro-nano mesoporous material prepared in Example 1 1 HNMR spectrum.

[0043] Figure 3The antifouling agent loading (TGA) in the micro-nano mesoporous material prepared in Example 1.

[0044] Figure 4 This is a SEM image of the sepiolite fiber before and after chemical loading of the antifouling agent in Example 1, wherein: Figure 4 (a) is the SEM image of sepiolite fiber before chemical loading of antifouling agent. Figure 4 (b) is the SEM image of sepiolite fiber after chemical loading of antifouling agent.

[0045] Figure 5 The dissolution rate of the antifouling agent in the micro-nano mesoporous materials prepared in Example 1 and Comparative Example 4 in artificial seawater.

[0046] Figure 6 The shallow sea antifouling effect of the marine antifouling composition of Example 3 and Comparative Example 5, wherein: Figure 6 (a) is a photograph of the sample sprayed with the marine antifouling composition in Example 3 after being in the sea for 2 months. Figure 6 (b) is a photograph of the sample sprayed with the marine antifouling composition in Example 3 after being in the sea for 9 months. Figure 6 (c) is a photograph of the sample sprayed with the marine antifouling composition in Comparative Example 5 after being in the sea for 2 months. Figure 6 (d) is a photograph of the sample sprayed with the marine antifouling composition in Comparative Example 5 after being in the sea for 9 months. DETAILED DESCRIPTION

[0047] The present invention is described in more detail below with reference to the accompanying drawings and in combination with the embodiments. The embodiments and features of the embodiments of the present invention may be combined or transformed with each other without conflict.

[0048] Artificial seawater was prepared according to the "Determination of cathodic disbonding resistance of paints and varnishes exposed to seawater (GB / T7790-2008)", and the release rate of DCOIT in it was determined by UV-visible near-infrared spectrophotometer; the evaluation of shallow sea antifouling effect was based on the "Shallow sea immersion test method for antifouling paint samples (GB / T 5370-2007)". Raw materials and reagents were purchased through normal commercial channels, strictly dried before use, and the water content was controlled to be no higher than 200ppm.

[0049] Example 1 The preparation steps of micro-nano mesoporous materials are as follows: S1, 80g of sepiolite fiber was ultrasonically dispersed in 2000mL of 10wt% dilute hydrochloric acid aqueous solution, magnetically stirred at 60℃ for 12h, and then saturated with NaHCO 3 The solution was washed until neutral, then transferred to a muffle furnace and calcined at 250°C for 1.5 h, and cooled for later use.

[0050] S2, 50mmol DCOIT, 55mmol 6-bromo-1-hexanol were dissolved in 300mL butyl acetate, and then 50mg KI was added, refluxed at 50℃ for 10h, and then 57.5mmol 2,6-diisocyanatohexanoic acid ethyl ester and 52mg T-12 were slowly added dropwise, and the reaction was continued for 8h. N 2 Atmosphere protection.

[0051] S3, grind and sieve the modified sepiolite fiber prepared in S1, take 27g 800 mesh powder, ultrasonically disperse it in 300mL butyl acetate, add it into S2 system, heat it to 70℃ and stir it for 5h, N 2 The obtained micro-nano mesoporous material structure is as follows: Figure 1 shown.

[0052] Example 2 The preparation steps of micro-nano mesoporous materials are as follows: S1. 100 g of sepiolite fiber was ultrasonically dispersed in 2000 mL of 8 wt% dilute hydrochloric acid aqueous solution, magnetically stirred at 50 °C for 10 h, and then saturated with NaHCO 3 The solution was washed until neutral, then transferred to a muffle furnace and calcined at 200°C for 2 h, and cooled for later use.

[0053] S2, 50mmol DCOIT, 55mmol 6-bromo-1-hexanol were dissolved in 250mL ethyl acetate, and then 50mg NaI was added, refluxed at 45℃ for 12h, and then 55mmol 2,5-diisocyanato ethyl valerate and 45mg T-12 were slowly added dropwise, and the reaction was continued for 7h. 2 Atmosphere protection.

[0054] S3, grind and sieve the modified sepiolite fiber prepared in S1, take 25g 2000 mesh powder, ultrasonically disperse it in 250mL ethyl acetate, add it into S2 system, heat it to 65℃ and stir it for 6h, N 2 The product is protected by the atmosphere and finally purified, dried, ground and stored.

[0055] Example 3 A marine antifouling composition comprises, by weight, 15 parts of the micro-nano mesoporous material described in Example 1, 25 parts of cuprous oxide, 6 parts of zinc pyrithione, 35 parts of hyperbranched zinc resin, 3 parts of modified rosin, 2 parts of polyethylene wax, 1 part of chlorinated paraffin, 8 parts of talc, 1 part of red iron oxide, 10 parts of xylene, and 5 parts of n-butanol.

[0056] Example 4 A marine antifouling composition comprises, by weight, 20 parts of the micro-nano mesoporous material described in Example 2, 25 parts of cuprous oxide, 4 parts of zinc pyrithione, 38 parts of hyperbranched zinc resin, 2 parts of modified rosin, 3 parts of polyethylene wax, 2 parts of chlorinated paraffin, 10 parts of talc, 12 parts of xylene, and 6 parts of n-butanol.

[0057] Comparative Example 1 The preparation steps of micro-nano mesoporous materials are as follows: S1. Dissolve 50mmol DCOIT and 55mmol 6-bromo-1-hexanol in 300mL butyl acetate, add 50mg KI, reflux at 50℃ for 10h, then slowly drop 57.5mmol ethyl 2,6-diisocyanatohexanoate and 52mg T-12, and continue to heat for 8h. 2 Atmosphere protection.

[0058] S2, after the sepiolite fiber was vacuum dried at 105℃ for 2h, 27g of 800-mesh powder was sieved, ultrasonically dispersed in 300mL butyl acetate, and then added to the S1 system, heated to 70℃ and stirred for 5h, with N 2 The product is protected by the atmosphere and finally purified, dried, ground and stored.

[0059] Comparative Example 2 4 g of sepiolite fiber was ultrasonically dispersed in 100 mL of 20 wt% hydrochloric acid aqueous solution, magnetically stirred at 60 °C for 12 h, and then saturated with NaHCO 3 After the solution was washed to neutrality, samples were taken to observe the fiber morphology.

[0060] Comparative Example 3 4 g of sepiolite fiber was ultrasonically dispersed in 100 mL of 10 wt% dilute hydrochloric acid aqueous solution, magnetically stirred at 60 °C for 12 h, and then saturated with NaHCO 3 The solution was washed until neutral, then transferred to a muffle furnace and calcined at 400-500°C for 2 h. After cooling, samples were taken to observe the fiber morphology.

[0061] Comparative Example 4 The preparation steps of micro-nano mesoporous materials are as follows: The sepiolite fiber was not pretreated in any way. 27 g of 800-mesh powder was directly taken and ultrasonically dispersed in 300 mL of butyl acetate containing 50 mmol DCOIT. The fiber was soaked at room temperature for 48 h and then dried for later use.

[0062] Comparative Example 5 A marine antifouling composition, except for using the micro-nano mesoporous material prepared in comparative example 4, the other raw materials and the dosage are the same as those in example 3.

[0063] Analysis shows that the FT-IR spectrum of the product obtained in Example 1 shows that-1 The Si-OH peak at 840 cm-1, which belongs to the modified sepiolite, is significantly weakened compared with that before polyurethaneization, but it still appears, indicating that there is redundancy in the reaction of silanol. -1 The C-Cl peak on the isothiazolinone ring appears at 2260 cm -1 The -NCO peak attributable to ethyl 2,6-diisocyanatohexanoate is significantly weakened after step S2 and almost disappears after step S3. -1 、1560cm -1 Newly added -NHCOO- peak nearby, 1100cm -1 、800cm -1 The newly added Si-OCO-bond stretching vibration peaks indicate that DCOIT has been successfully covalently grafted to the sepiolite fiber through the polyurethane bridging unit ( Figure 2 middle 1 This can also be corroborated by HNMR spectrum).

[0064] TGA thermal gravimetric loss (such as Figure 3 As shown in the figure, it was found that the heat resistance of DCOIT was improved after grafting, and the drug loading rate of the fiber was 60.6% (higher than the patent with publication number CN115141508B), achieving a large flux load. Compared with concentration enrichment detection such as dialysis dissolution, thermal gravimetry can more accurately and intuitively reflect the weight loss status at each temperature stage, eliminating the influence of some guest molecules entering the receptor pores due to physical adsorption, which leads to distortion of chemical drug loading data (mainly manifested as high) (the strength of intermolecular interactions can have stress responses to different temperatures, the physical adsorption force is small, and desorption and weight loss occur in the low temperature zone, making it easy to identify and distinguish).

[0065] In addition, SEM showed that the sepiolite used in Example 1 had a complete and relatively loose fiber morphology (even unbundled into single fibers) after S1 acid etching + calcination, with a smooth surface and a length of more than 4 μm (e.g. Figure 4 After step S3, the fiber surface roughness increases (as shown in Figure a). Figure 4 As shown in Figure b), it is covered with dot-like spots, which also indirectly confirms the successful connection of DCOIT.

[0066] The peak shifts of the synthetic compound in Example 2 in the FT-IR spectrum are basically the same as those in Example 1. The drug loading measured by TGA is 54.8%. The reason may be that the modified sepiolite fiber used is relatively short and thick (2000 mesh), and the loading of the "comb-tooth" antifouling agent long chain is slightly lower.

[0067] Correspondingly, if the sepiolite is not treated in advance, such as in Comparative Example 1, the fiber crystals are dense, the intrinsic silanol groups in the superficial surface and internal cavities are few and the activity is low, and the free water is not completely calcined, resulting in the -NCO group being consumed without value, the number of "bridges" of polyurethane units is limited, and a large amount of DCOIT quaternary ammonium alcohol salts cannot be covalently bonded to the sepiolite molecules, and the chemical drug loading is less than 30%. During TGA detection, a large proportion of abnormal burning loss occurs in the low temperature zone (similar to Comparative Example 4), which also reflects that the guest molecules are still mostly coupled in the form of physical adsorption.

[0068] In order to investigate the effects of hydrochloric acid solubility and calcination temperature in step S1 on the pore structure of sepiolite, we specially designed comparative examples 2 and 3. Under SEM, it can be observed that when the hydrochloric acid concentration increases from 15% to 20wt%, the fiber begins to show a decrease in specific surface area, pore blockage, and fiber breakage; and when calcined above 400℃, the crystal water (and even hydroxyl water) in the fiber is continuously lost, and the pores gradually collapse.

[0069] Depend on Figure 5 It is not difficult to see that the release of DCOIT in Example 1 is basically stable after about 14 days in artificial seawater, and it has been "progressively" dissolved (almost close to constant speed) in the subsequent 98 days. The dual degradation process of the polyurethane covalent bridging site and the self-polishing of the hyperbranched zinc resin play a good role in the "locking → unlocking" slow release regulation. The weak intermolecular force in Comparative Example 4 is not enough to support the long-term loading of DCOIT in the receptor pore (stable section 14-49 days). As the immersion time increases, the drug release increases significantly after 50 days. It is easy to foresee that at this rate, the drug dosage will be exhausted in the near future.

[0070] Figure 6 The difference in antifouling performance in a certain sea area of ​​the South China Sea after the samples were sprayed with the marine antifouling compositions in Example 3 and Comparative Example 5 was clearly reflected. After the summer and autumn (more than 9 months) when marine organisms reproduced vigorously, the surface of the coating in Example 3 was smooth and clean, and the influence of the sample edge effect was eliminated. There were few species climbing in the central area (such as Figure 6 In contrast, in Comparative Example 5, a large number of barnacles and mussels grew, occupying nearly 1 / 3 of the area (as shown in Figure b). Figure 6 In fact, the killing effect of comparative example 5 in the first two months was not significantly different from that of embodiment 3 ( Figure 6 C-graph Vs. Figure 6 Figure a), however, due to the difference in the antifouling agent system, in Comparative Example 5, DCOIT is physically adsorbed by sepiolite alone, and it is difficult for sepiolite to restrict its slow release for a long time, and it gradually becomes exhausted after a certain period of time; thanks to the strong chemical bonding, the antifouling system of Example 3 has a "zero-order" drug release function. After the "bridge" connecting the sepiolite fibers slowly disintegrates, DCOIT is gradually "unlocked" to exert a long-term effect.

[0071] In summary, through simple hydrothermal etching, quaternization, silanol amino esterification and other mature methods, the DCOIT-derivative guest molecules are firmly encapsulated in the sepiolite receptor container, which provides a desirable reference for the high-level utilization of inorganic powders and the high-throughput chemical loading (60.6%) of marine antifouling agents. Subsequent micro-nano mesoporous material matrices rich in active hydroxyl groups, amine groups and other graftable functional groups such as halloysite, montmorillonite, zeolite, gas silica, and organic metal frameworks can be modified in this way. The marine antifouling composition prepared with this organic-inorganic hybrid slow-release system has good compatibility among the components, and has high efficiency, broad spectrum, low toxicity and long-lasting properties. It is suitable for antifouling needs in multiple scenarios such as sports ships, offshore ranches, and static platforms.

[0072] The contents of the above embodiments should be understood as these embodiments are only used to more clearly explain the present invention, rather than to limit the scope of the present invention. After referring to the present invention, the modifications of various equivalent forms of the present embodiment inspired by the same technical personnel fall into the protection scope defined by the appended claims of the present invention.

Claims

1. An antifouling agent, characterized in that: Contains the following molecular structure: ; In formula I, m and n are respectively non-zero natural numbers, and X is a halogen.

2. A micro-nano mesoporous material, characterized in that: The invention comprises a micro-nano mesoporous material matrix and the antifouling agent according to claim 1, wherein the activated silanol groups in the micro-nano mesoporous material matrix are covalently linked to -NCO units in the antifouling agent.

3. The micro-nano mesoporous material according to claim 2, characterized in that: The micro-nano mesoporous material matrix includes one or more of sepiolite, halloysite, montmorillonite, zeolite, gas silica and organic metal framework.

4. The micro-nano mesoporous material according to claim 3, characterized in that: When the micro-nano mesoporous material matrix is ​​sepiolite, the particle size of the micro-nano mesoporous material matrix is ​​200-3000 meshes.

5. The micro-nano mesoporous material according to any one of claims 2 to 4, characterized in that: The preparation method of the micro-nano mesoporous material comprises the following steps: S1, subjecting the micro-nano mesoporous material substrate to hydrothermal acid etching, cleaning, calcination, and cooling for standby use; S2, dissolving the DCOIT-like derivative and the halogenated fatty alcohol in a solvent, heating to reflux, then dropping a mixture of diisocyanate and a catalyst, and continuing the reaction at a heat preservation temperature; S3, grinding and dispersing the modified matrix of the micro-nano mesoporous material obtained in S1 in a solvent, adding it into the S2 system to react at a high temperature, and then purifying, drying, grinding and storing it.

6. The micro-nano mesoporous material according to claim 5, characterized in that: The molar ratio of the DCOIT-like derivative, the halogenated fatty alcohol, and the diisocyanate in S2 is 1:(1-1.1):(1.1-1.15).

7. The micro-nano mesoporous material according to claim 5, characterized in that: The structure of the DCOIT-like derivative is as shown in Formula II: ; In formula II, R1 and R2 are independently selected from -H, -Cl, -Br, and -I; R3 is selected from any one of -H, aliphatic alkyl, aralkyl, alkoxy, alkenyl, and alkynyl.

8. The micro-nano mesoporous material according to claim 5, characterized in that: The halogenated fatty alcohol includes one or more of chlorinated, brominated, iodinated, and fatty alcohols containing 1 to 8 carbon atoms; The diisocyanate is an α, ω-terminated diisocyanate fatty acid ester and its derivatives, including one or more of 2,3-diisocyanatopropionate, 2,4-diisocyanatobutyrate, 2,5-diisocyanatovalerate, 2,6-diisocyanatohexanoate, 2,7-diisocyanatoheptanoate, 2,8-diisocyanatooctanoate, 2,9-diisocyanatononanoate, 2,10-diisocyanatodecanoate and their derivatives.

9. A marine antifouling composition, characterized in that The invention comprises 10 to 30 parts of the micro-nano mesoporous material according to any one of claims 2 to 8, and further comprises 25 to 45 parts of cuprous oxide, 5 to 10 parts of zinc pyrithione, 30 to 40 parts of hyperbranched zinc resin, 3 to 5 parts of modified rosin, 1 to 3 parts of polyethylene wax, 0 to 3 parts of chlorinated paraffin, 0 to 10 parts of filler, 0 to 3 parts of red iron oxide, and 10 to 20 parts of organic solvent.

Citation Information

Patent Citations

  • Microencapsulation of biocides and antifouling agents

    CN102293198B

  • A moisture-curing polyurethane antifouling coating for fishing nets and its preparation method

    CN110835495B

  • A long-lasting antifouling agent supported on a metal-organic framework and its preparation method

    CN115141508B

  • Control release composition

    CN1229022C

  • Microencapsulated biocides and coating compositions

    JP2008513475A

Cited By

  • Dual-degradable resin and preparation method thereof, antifouling agent system, marine antifouling composition and application thereof

    CN121851270A

  • Antifouling agent, micro-nano mesoporous material, and marine antifouling composition

    WO2026166111A1